2014
DOI: 10.1039/c4cp02204a
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the hydrogen storage capacity of TiFe by utilizing clusters

Abstract: The titanium iron (TiFe) alloy is a notable hydrogen storage material which can operate at ambient temperature. However, low hydrogen storage capacity is a major drawback that is needed to be overcome. Enhancement of the hydrogen capacity of TiFe is considered by utilizing TiFe clusters within the density functional theory. Calculations reveal that TiFe clusters can absorb large amounts of hydrogen. Furthermore, the desorption energies of Ti1Fe1H6 are lower than that of bulk TiFeH where the physical origins of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…The ground state structures of Ti N Fe N (N = 1‐5) clusters are shown in Figure 1. The binding energy of TiFe clusters is summarized in Table 1 which, has good agreement with the previously reported literatures 20 . It is experimentally reported that Ti prefers to substitute Zr due to similar electronic configuration and less electronegativity difference between Ti and Zr 27 .…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The ground state structures of Ti N Fe N (N = 1‐5) clusters are shown in Figure 1. The binding energy of TiFe clusters is summarized in Table 1 which, has good agreement with the previously reported literatures 20 . It is experimentally reported that Ti prefers to substitute Zr due to similar electronic configuration and less electronegativity difference between Ti and Zr 27 .…”
Section: Resultssupporting
confidence: 89%
“…The binding energy of TiFe clusters is summarized in Table 1 which, has good agreement with the previously reported literatures. 20 It is experimentally reported that Ti prefers to substitute Zr due to similar electronic configuration and less electronegativity difference between Ti and Zr. 27 Therefore, Ti atom is substituted with Zr atom within TiFe clusters.…”
Section: Geometry and Binding Energymentioning
confidence: 99%
See 2 more Smart Citations
“…In order to overcome this problem, different approaches have been investigated. They include pulse current-assisted reaction [4], ball milling [3,5], plastic deformations [6], and utilizing clusters [7]. …”
Section: Introductionmentioning
confidence: 99%